The correlation between the sagittal lumbopelvic alignments in standing position and the risk factors influencing low back pain - Chanplakorn, Pongsthorn (PAGEPress Publications, 2012)
Low back pain (LBP) is the most common health problem. Many factors have been demonstrated to be fundamental risk factors of LBP such as body mass index (BMI), age and sex. However, so far there have been few studies demonstrating the association between lumbo-pelvic alignment (LPA) and these factors. This present study was aimed to clarify the correlation between the LPA and the risk factors contributing to LBP. Standing lateral X-rays were taken from 100 healthy volunteers (70 males and 30 females) with no history of low back pain before their participation. Average age of subjects was 33.3±6.8 years (rang 21–50). Mean body weight was 59.1±7.9kg (range 40–82), mean body height was 163.6±7.2 cm (range 145–178) and mean BMI was 22.1±2.4 kg/m(2) (range 18.0–29.3). The LPA was classified into 3 types according to the recently proposed pelvic orientation guidelines. No direct correlation was found between the pelvic orientation and age or BMI. Each LPA type was associated with sex but not BMI and age (P=0.00, 0.71, and 0.36, respectively). The results from this study demonstrated the differences in LPA between male and female, and also confirmed that the sagittal orientation of the pelvis remained constant in adults. The high prevalence of LPA type 1 in males may reduce the occurrence of LBP in obese male individuals.